Modeling Consumer Preferences and Price Sensitivities from Large-Scale Grocery Shopping Transaction Logs - Wan, Mengting; Wang, Di; Goldman, Matt; Taddy, Matt; Rao, Justin; Liu, Jie; Lymberopoulos, Dimitrios; McAuley, Julian (26th International Conference on World Wide Web, 2017)
In order to match shoppers with desired products and provide personalized promotions, whether in online or offline shopping worlds, it is critical to model both consumer preferences and price sensitivities simultaneously. Personalized preferences have been thoroughly studied in the field of recommender systems, though price (and price sensitivity) has received relatively little attention. At the same time, price sensitivity has been richly explored in the area of economics, though typically not in the context of developing scalable, working systems to generate recommendations. In this study, we seek to bridge the gap between large-scale recommender systems and established consumer theories from economics, and propose a nested feature-based matrix factorization framework to model both preferences and price sensitivities. Quantitative and qualitative results indicate the proposed personalized, interpretable and scalable framework is capable of providing satisfying recommendations (on two datasets of grocery transactions) and can be applied to obtain economic insights into consumer behavior.